Estrous behavior and the estrus-to-ovulation interval in Nelore cattle (Bos indicus) with natural estrus or estrus induced with prostaglandin F2 alpha or norgestomet and estradiol valerate - Pinheiro, O. L.; Barros, C. M.; Figueiredo, R. A.; do Valle, E. R.; Encarnacao, R. O.; Padovani, C. R. (Elsevier B.V., 1998)
Estrous behavior and the estrus-to-ovulation interval are essential for estimating the best time to artificially inseminate cattle. Because these parameters are not well characterized in the Nelore breed (Bos indicus), the main purpose of the this study was to determine the estrus-to-ovulation interval in Nelore heifers and cows with natural estrus or with estrus induced by treatments with PGF2 alpha or norgestomet and estradiol valerate (NEV). The cows and heifers were observed continuously (24 h a day) to determine the onset of estrus and to study estrous behavior in the cows. Ten hours after the start of estrus the ovaries were scanned every 2 h by ultrasonography to monitor the dominant follicle until ovulation. Blood samples were collected periodically to determine progesterone levels by RIA. Administration of PGF2 alpha (2 injections, 11 days apart) did not induce estrus in most Nelore females in spite of the presence of functional CL, indicated by progesterone concentrations above 6.0 ng/ml in 25 of 28 animals. Treatment with NEV induced high sexual receptivity in cows (10/11), but only 66% ovulated. Cows with natural or induced estrus exhibited behavioral estrus of 10.9 +/- 1.4 h, and ovulation occurred 26.6 +/- 0.44 h (n = 26) after the onset of estrus. In most of the cows (53.8%) estrus began at night (between 1801 and 600 h), and 34.6% it started and finished during the night. It is concluded that in Nelore females ovulation occurs approximately 26 h after the onset of estrus. Additionally, estrous behavior is shorter than in European breeds, and there is a high incidence of estrus at night, which makes it difficult to detect and, consequently, impairs Al in Nelore cattle. The observation that a high percentage of Nelore females with an active CL did not respond to usual dosages of PGF2 alpha warrants further investigation. (C) 1998 by Elsevier B.V.
Keywords: estrus; ovulation; progesterone; Bos indicus; ultrasound